New records of lichens from the Russian Far East. IV. The lichens of limestone outcrops of the southern part of the Russian Far East ... - Davydov, Evgeny A.; Ryzhkova, Polina Yu.; Frolov, Ivan V.; Galanina, Irina A.; Yakovchenko, Lidia S. (Zenodo, 2023)
The new records of the lichens of limestone outcrops in the southern part of the Russian Far East (Primorye Territory and Sakhalin Region) are presented. Among them, Catillaria detractula , Gyalecta jenensis , Myriolecis semipallida , Physconia jacutica , Sarcogyne regularis , Thyrea confusa , Verrucaria caerulela , V. viridula and Xanthoria calcicola are newly reported for the Russian Far East; Acarospora glaucocarpa , A. macrospora , Lecanora valesiaca , Protoblastenia calva and Thelidium decipiens are newly reported for the southern part of the Russian Far East. Xanthocarpia crenulatella is a new species for Sakhalin Region. Diagnostic traits of the species, peculiarities of the material from the Russian Far East, distribution, ecology and comparison with the closest species are given. ... : We are grateful to Sergey S. Yakovchenko and Alexander V. Fedonyuk for their help with the organization of field work in Primorye Territory in 2017 and 2022. The study of E.A. Davydov and P.Yu. Ryzhkova was funded by the program «Priority-2030» of Altai State University. I.V. Frolov worked within the framework of the national project of the Institute Botanic Garden (Russian Academy of Sciences, Ural Branch) and the state assignment of Ministry of Science and Higher Education of the Russian Federation of the Botanical Garden-Institute FEB RAS (theme No. 122040800089-2). The research of L.S. Yakovchenko and I.A. Galanina was carried out within the state assignment of Ministry of Science and Higher Education of the Russian Federation of the Federal Scientific Center of East Asian Terrestrial Biodiversity FEB RAS (theme No. 121031000117-9). ...